The Influence of Brand Image, Electronic Word of Mouth, and Product Quality on Consumer Purchasing Decisions For Marina Products in Batam City - Desmirasari, Resa; Hikmah, Hikmah (J-MAS (Jurnal Manajemen dan Sains), 2024)
The objective of this study is to ascertain the impact of brand image, electronic word of mouth, and product quality on consumer purchase decisions. The study was carried out in Batam City in 2023 and using a quantitative research design. The population consisted of 204 individuals, and a random sample technique was utilised for participant selection. Data was collected via a questionnaire and analysed using multiple linear regression analysis. The research findings indicate that brand image has a substantial and favourable impact on purchasing decisions, as evidenced by a significant p-value of 0.000 <0.05. Additionally, electronic word-of-mouth (EWOM) also has a significant positive influence on purchasing decisions, supported by a p-value of 0.009 <0.05. Furthermore, product quality is found to have a significant positive effect on purchasing decisions, with p-value 0,000< 0,05. The research findings indicate that brand image, electronic word-of-mouth (eWOM), and product quality have a significant impact on purchase decisions. The statistical analysis shows a significant relationship with a p-value of 0.000, which is less than the threshold of 0.05. Additionally, the computed F-value of 208.863 is greater than the critical value of 2.65 (based on the F table). The Adjusted R Square value of 75.8% demonstrates the impact of brand image, eWOM, and product quality on purchase decisions. The remaining 24.2% is attributable to other variables in this study.